Die klassieke retoriek as basis vir hedendaagse openbare spraakkommunikasieleerinhoude - Frederick Terblanche (Communicare)
This article explores a number of characteristics of the conceptual structure and teaching of classical rhetoric, and indicates that the subject contents of rhetoric were based at the outset on certain principles and con texts of public communication events in the world in which people lived. This approach to the identification of the subject contents of oral communication has not changed substantially over time, nor have the basic categories by which public communication was originally distinguished as a field of study. What has changed considerably, is the human concept of the fundamental nature and scope of communication principles and contexts, the perspectives from which it is approached and its ontological and philosophical basis. The ordering and systemisation of these are naturally expressed in a more comprehensive and scientific conceptual system than was the case in the classical era. In order to gain a thorough understanding of the complex system, however, It is necessary to study its classical rhetorical roots.